SOUND STYLE IN THE POETRY ANTHOLOGY TIRANI DAN BENTENG BY TAUFIQ ISMAIL: A STYLISTIC STUDY BASED ON PRADOPO'S THEORY - Fitriani, Fitriani; Rapi, Muhammad; Nensilianti, Nensilianti (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to describe the sound style in the poetry anthology Tirani dan Benteng by Taufiq Ismail. Using a qualitative approach with a descriptive method, this research is based on the Tirani dan Benteng anthology, published by Yayasan Indonesia (2001), consisting of 172 pages. The findings, based on Pradopo's stylistic approach, reveal that the poems in this anthology contain various sound styles, including alliteration, assonance, initial rhyme, end rhyme, middle rhyme, and internal rhyme. Additionally, the study identifies figurative sound elements in the form of symbolic sounds, as well as sound orchestration, encompassing euphony and cacophony. This research is expected to enhance readers' understanding of the role of sound style in poetry analysis.